The electroacoustic performance of digital noise reduction systems in commercial hearing aids with Malay speech-plus-noise test signals - Nurul Najwa Nazri,; Wan Syafira Ishak,; Chong Foong Yen, (Penerbit Universiti Kebangsaan Malaysia, 2024)
One of the most frequent complaints of individuals with hearing impairment is listening comfort in noisy environments. In order to improve listening comforts in background noise, digital noise reduction (DNR) systems are incorporated into hearing aids (HAs). Each hearing aid manufacturer has its proprietary algorithm for the DNR system. The amount of attenuation (dB) provided by the DNR system can be quantified using the hearing aid analyser. However, the standard test signals in the hearing aid analyser could not quantify the attenuation of DNR for speech mixed with noise signals. Therefore, this study aimed to (i) develop speech-plus-noise test signals that incorporate Malay sentences and (ii) quantify the efficacy of DNR systems in commercial hearing aids using the newly developed test signals. Six different brands of hearing aids with identical technology but from different manufacturers were subjected to electroacoustic testing utilising newly created Malay speech-in-noise test signals with and without DNR enabled. The total root-mean square (RMS) gain reduction for each HA was calculated. The results show that the types of noise, the signal-to-noise ratio and the gender of the speaker have a significant effect (p<0.05) on the amount of gain reduction in the HA output as a result of the DNR system in each HA . In conclusion, the newly developed Malay speech-in-noise test signals can be used to verify the efficacy of DNR system in commercial hearing aids.